STRATEGI ASEAN DALAM MENGHINDARI RIVALITAS HEGEMONI ‘BIG POWER STATES’ DI KAWASAN ASIA TENGGARA - Husna, Rafika (Indonesian Journal of International Relations, 2025)
This study aims to analyze ASEAN's strategy in facing the potential hegemonic rivalry among big power states in Southeast Asia. Employing a qualitative research method using secondary data, this study is grounded in the expanded balance of power theory from the neorealist/structural realist school of thought, with ASEAN's hedging strategy as its overarching framework. The research findings indicate that ASEAN adopts a hedging strategy through four main dimensions: soft bandwagoning/strategic engagement, soft balancing (internal), strategic ambiguity/dual positioning, and risk management strategy. These dimensions are manifested in initiatives such as ASEAN Centrality, the ASEAN Outlook on the Indo-Pacific (AOIP), the Zone of Peace, Freedom, and Neutrality (ZOPFAN) as a multilateral security framework, and efforts to balance institutions and ideas. In conclusion, ASEAN can effectively avoid hegemonic rivalry in the region by maintaining a collaborative and adaptive hedging strategy